Nutritional status of children with cerebral palsy in a selected tertiary care hospital - Sultana, M. Afiya; Chowdhury, M. Jahangir; Farhad, A. F. M.; Adnan, Mohammad Ahad; Khanam, Wahida; Akter, M. Asma (International Journal of Contemporary Pediatrics, 2023)
Background: Nutritional status in children with chronic disease like cerebral palsy is crucial in growth and development. This study was conducted with the aim of assessing nutritional status of children with CP by using anthropometric indices and few associated factors. Methods: This cross-sectional study was conducted in ICMH, Dhaka from July 2020 to June 2021. A total of 30 children underwent proper history taking and thorough anthropometric examinations. Twenty-four hours dietary recall method was used for estimating approximate calorie intake. Results: Out of 30 children two thirds age was under 60 months and mean±SD age was 59.2±33.1 months. 60.0% children were male and majority (86.7%) of children were found calorie intake ≤50 percent of adequate calorie intake. Most (83.3%) of studied children presented with spastic quadriplegia, in according to age, 2 group were created (<60 months & ≥60 months). In children under 5 years age, 75.0% were severely wasted, 35.0% were severely stunted, 85.0% were severely underweight and 75.0% were severely malnourished. In ≥5 years, 60.0% were severely stunted and 90.0% were underweight or thin. Wasting andhad significant association with swallowing difficulty and inadequate calorie intake in under 5 years age group and stunting had significant association with those factors in ≥5 years age group. Conclusions: This study shows that undernutrition affects a large number of children with CP in a selected tertiary care hospital. Risk of severe undernutrition increases with swallowing difficulty.